Story of Conservation: Integrating Ethnobotanical Knowledge, Healer, and Sacred Area in Daulu–Karonese, North Sumatera - Riziqo, Reza Anggi; Purba, Kerin Nasrani Kislow Br; Surbakti, Brando Rivaldi; Fahlisyah, Mutiara; Purba, Intan Sarapina; Sembiring, Sri Alem Br. (PERSPEKTIF, 2024)
This article aims to explain the conservation mechanisms of a community to protect village forests; and how actors can create communities that maintain the value of forests as spaces for life's needs. This article focuses on ethnobotanical knowledge (especially medicines), transmission, healing practices, and forest protection mechanisms. The relationship between these four things is a story of sustainable conservation, both in-situ and ex-situ. This mechanism turns out to be related to mythology, sacredness, and sacred areas. This phenomenon was found in Karonese, Daulu Village, North Sumatra, Indonesia. The cognitive anthropology approach with the concept of culture in mind becomes an important tool for analyzing how knowledge is constructed and transmitted. Ethnographic research methods with an emic approach, participant observation, in-depth interviews with key informants, and completeness of filed notes are one way to capture the native point of view. Data analysis was carried out qualitatively through ongoing analysis. The conclusion of the study found that the capacity of actors, especially healers, and the transmission of ethnobotanical knowledge, especially medicines, and the survival of mythological stories and values about sacred areas have consequences for the sustainability of conservation of what they call the kerangen kuta or village forest.